PEMAHAMAN MAHASISWA AKUNTANSI TERKAIT PENGGUNAAN SOFTWARE AKUNTANSI DALAM PELAPORAN KEUANGAN - Anggerwati, A. Indah (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
The development of information technology has brought significant changes to the world of accounting education and the profession. The use of accounting software such as MYOB, Accurate, and Microsoft Excel has now become an essential skill that accounting students must master to compete in an increasingly digital workplace. This study aims to analyze accounting students' level of understanding of accounting software usage and the factors that influence it. The study used a qualitative approach with a phenomenological design, which focused on an in-depth understanding of students' experiences and perceptions in using accounting software. Data was collected through a Google Form questionnaire distributed to 30 students in the Accounting Study Program, Faculty of Business, Andi Sapada Institute of Social and Business Sciences, Parepare, who had taken a computerized accounting course. The results showed that the majority of respondents were female (76.7%), and almost all (96.7%) had experience using accounting software. Microsoft Excel was the most widely used software by students, at 73.3%, followed by Accurate (46.7%) and MYOB (23.3%). Most students (56.7%) had a good understanding of accounting software usage, although a small percentage (6.7%) had a low or high level of understanding. Furthermore, approximately 90% of students had used accounting software during their studies, indicating that technology has been integrated into accounting learning. The conclusion of this study indicates that accounting students have a fairly good understanding of accounting software usage, but still need improvement in practical skills and financial data analysis. Factors such as learning motivation, teaching methods, and the availability of computer laboratory facilities influence student understanding. Therefore, a more interactive and practice-based learning strategy is needed to ensure students' optimal mastery of accounting software and readiness to face the demands of the modern workplace.